Performance Evaluation of SMEs-A Special Focus on Small Size of Businesses at Tangail District in Bangladesh (Global Journal of Management and Business Research, 2013)
Bangladesh is one of the developing countries in the world and which is struggling to overcome the impediments of economy. As a part of it is highly depends on the enhancement of Small and Medium Enterprises (SMEs). So, now-a-days it can be considered as a vital instrument for our economy to be dynamic. In this paper an attempt has been made to review the present state (in 2012) of Small and Medium Enterprises in Bangladesh. This paper has been prepared based on a sample of 200 Small Size of Businesses (SSBs) in different parts of Tangail district and the performance has been measured on ten broad indicators which incorporates several sub indicators. From the analysis it has been found that this sector is growing rapidly and playing significant roles in the economy of Bangladesh as to alleviate the rate of poverty by creating new hope for the unemployed. It has also been caught sighted that this sector having some of its deviations to reach the international level of standard. At the end of this paper, it provides worth mentionable suggestions against the deviations.
Keywords: small size of businesses; indicators; performance evaluation; average growth